Conversion of bio-char to CaC2 at low temperatures-morphology and kinetics. (31st December 2018) - Li, Zhengke; Liu, Zhenyu; Wang, Renxing; Guo, Xiaojin; Liu, Qingya
Graphical abstract: Highlights: Bio-char can be converted to the solid CaC2 at a high reaction rate around 1650 °C. CaC2 layer formed between reactants agglomerates the particles without melting. CaC2 synthesis is under reaction control but is slightly affected by reactants size. A R3 model is developed considering changes in activation energy and particle size. Abstract: The conversion of bio-char to CaC2 is a potential way to achieve the production of high-value-added chemicals from biomass. The unique properties of bio-char, such as its fine particles, high activity, and low ash content, provide a high reaction rate, low reaction temperature, and high CaC2 purity, which increase the feasibility of converting bio-char to CaC2 . This work investigates the morphological behaviors of the solid reactants and the products, as well as the reaction kinetics, in terms of changes in activation energy and the particle size of the reactants. The experiments were carried out using a thermal gravimetric analyzer coupled with a mass spectrometer (TG-MS) at temperatures lower than 1700 °C using corncob char and CaO as the starting materials. The TG-MS data and kinetics modeling show that at temperatures of 1400–1700 °C, the reaction of corncob char and CaO with a particle size of 22–114 μm is predominantly under reaction control, but is slightly affected by the size of the reactants. During the course of the reaction, the reacting solids agglomerate via the formation of CaC2 without apparent melting.